PENGARUH BUERGER ALLEN EXERCISE TERHADAP PENINGKATAN NILAI ANKLE BRACHIAL INDEX PADA PASIEN DIABETES MELITUS TIPE II DI RUMAH SAKIT ILYAS TARAKAN - Novitayanti; Nurhayanti; Betty (Jurnal Stethoscope, 2025)
Diabetes mellitus (DM) is a group of metabolic diseases characterized by high blood glucose levels, or hyperglycemia. The purpose of this study was to determine the effect of Buerger Allen exercise on improving ankle-brachial index (ABI) scores in type II diabetes mellitus patients at Ilyas Hospital, Tarakan. The research method used was quantitative, using a quasi-experimental design, with a one-group pretest and posttest. The treatment group was observed before the intervention and then again after the intervention. The population was 25 individuals, and the sample size used a total sampling technique with a sample size of 25 individuals. The results of the study showed that the average Ankle-Brachial Index (ABI) value before and after Buerger Allen exercise in patients with type II diabetes mellitus at Ilyas Naval Hospital, Tarakan, in 2025 was 1.12000 with a standard deviation of 0.33166. Based on the results of the paired simple T-test, the p-value was 0.000 <α = 0.05. Therefore, the research hypothesis was accepted. It can be concluded that there is an effect of Buerger Allen Exercise on increasing the Ankle-Brachial Index value in patients with type II diabetes mellitus at Ilyas Naval Hospital, Tarakan, in 2025.